Genome-Wide Identification, Structural, and Gene Expression Analysis of BRI1-EMS-Suppressor 1 Transcription Factor Family in Cucumis sativus - Ma, Si; Ji, Tingting; Liang, Meiting; Li, Shihui; Tian, Yongqiang; Gao, Lihong (Frontiers in Genetics, 2020)
BRI1-EMS-suppressor 1 (BES1) is an essential regulator in the downstream of BR signaling and plays important roles in plant stress response, growth and development. To date, the regulation mechanism of BES1 transcription factors have been identified and elucidated in model plants Arabidopsis and rice. However, little information is available regarding the BSE1 family in Cucumis sativus. Therefore, this study conducted a genome-wide analysis of BES1 genes in cucumber. In cucumber, a total of six CsBES1 genes were identified, and their phylogenetic relationship, genes structures and cis-elements in promoters were studied. CsBES1 genes were distributed on four of seven chromosomes. Gene structure analysis showed that the intron-exon model of CsBES1 genes were conserved and CsBES1 protein contained DUF822 conserved motif. Promoter cis-elements prediction showed that there were plenty of developmental-, stress- and hormones-related elements were found in promoter regions of CsBES1 genes. Meanwhile, BES1 was divided into three group (I, II and III) on the basis of phylogenetic relationship analysis in six plant species. In addition, CsBES1 genes expression patterns were confirmed by transcription database and qPCR analysis showed that not only CsBES1 genes revealed tissue-specific expression, but also CsBES1 genes were induced or suppressed in roots and leaves under salt, drought and cold stress treatments, implying that CsBES1 genes play important roles in plant adaption to abiotic stresses. In summary, genome-wide identification, phylogeny, gene structure and expression profile analysis of CsBES1 genes in cucumber provided a solid theoretical information for further functional study of CsBES1 genes and further facilitated the molecular breeding of cucumber.